Adequacy of County Financial Allocations for Essential Medicines in Rural Public Health Facilities in Mandera County, Kenya - Ali Hassan Etho; Fredrick Kimemia; Lillian Muiruri (East African Journal of Health and Science, 2026)
Essential medicines are fundamental to effective healthcare delivery, yet inadequate financial allocations continue to undermine their availability in rural public health facilities in Kenya. This study assessed the adequacy of county financial allocations for essential medicines in rural public health facilities in Mandera County, Kenya, between 2022 and 2024. A mixed-methods cross-sectional design was employed involving 79 healthcare personnel drawn from dispensaries, health centres, and sub-county hospitals, alongside 12 key informant interviews with county and sub-county officials responsible for finance, procurement, and pharmaceutical services. Quantitative data were collected using structured questionnaires and analysed using descriptive statistics, Pearson correlation, and multiple regression analysis, while qualitative data were analysed thematically. The findings revealed that 64.6% of respondents perceived county financial allocations as inadequate and 35.4% as very inadequate, with none reporting the allocations as adequate. All participating facilities experienced funding gaps, and most received only 51–75% of their quantified medicine requirements from the Kenya Medical Supplies Authority (KEMSA). Inferential analysis demonstrated a strong positive relationship between the adequacy of county financial allocations and essential medicine availability (r = 0.741, p < 0.05). Multiple regression analysis further identified financial allocation as the strongest predictor of medicine availability (β = 0.463, p < 0.001), while the overall regression model was statistically significant (F = 42.138, p < 0.001) and explained 67.9% of the variation in medicine availability (R² = 0.679). The study concludes that county financial allocations during the study period were insufficient to meet facility-level medicine requirements, thereby compromising the continuous availability of essential medicines. Strengthening county budgetary allocations, aligning financing with KEMSA quantification requirements, and protecting medicine budgets from competing expenditure priorities are essential to improving medicine security and healthcare service delivery in rural public health facilities.